Efficacy of passive ultrasonic irrigation in removing root filling material during endodontic retreatment - Carina MICHELON; Marina FRIGHETTO; Pauline Mastella LANG; Mariana De Carlo BELLO; Rafael PILLAR; Geraldo Fagundes SERPA; Carlos Alexandre Souza BIER
Abstract Introduction The aim of endodontic retreatment is to remove the previous root filling materials completely to allow for the subsequent steps of cleaning, canal shaping and filling replacement. Objective To evaluate the efficacy of passive ultrasonic irrigation (PUI) in the removal of residual root filling material after removing the bulk of the root filling with nickel-titanium rotary instruments. Material and method Eighteen mesial isthmus-containing roots of human mandibular molars were prepared and filled. The root canal filling was removed with the ProTaper Retreatment system and K-files. The specimens were randomized into 2 groups (n = 9), both irrigated with 2.5% NaOCl and 17% EDTA. In the conventional group, an irrigation syringe was used. In the PUI group, the PUI technique was used. The roots were sectioned longitudinally and evaluated under stereomicroscopy. Student's t test was used to compare groups and the general linear model was used to compare the apical, cervical, and middle root thirds within each group, in regard to the percentages of remaining residual filling material. Result There was no statistically significant intergroup difference, irrespective of which root third was evaluated (P > 0.05). In the PUI group, the apical third showed a significantly higher percentage of residual filling material, in comparison with the cervical (P = 0.038) and middle (P = 0.029) thirds. Conclusion The PUI technique was not more effective than the conventional irrigation technique in removing residual root filling material during endodontic retreatment in root canals with a complex anatomy.